1983
DOI: 10.3758/bf03213469
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of affect in the spacing effect?

Abstract: In Experiments 1 and 2, after studying a list containing connotatively neutral words that were presented once or were presented at various spacing intervals, subjects either attempted free recall or made affective judgments of the study-list targets along a pleasant/unpleasant dimension. Spacing effects occurred in recall, and massed items were judged to be more unpleasant than once-presented and spaced words. In the third experiment, subjects studied homogeneous lists composed of either connotatively good wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
35
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 12 publications
6
35
2
Order By: Relevance
“…Kahana and Greene (1993) replicated the findings of Elmes et al (1983), but demonstrated that the spacing effect in free recall also was eliminated with homogeneous lists that were affectively neutral. Thus, the spacing effect in free recall was eliminated when list words consisted entirely of four-footed animals or entirely of occupations.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…Kahana and Greene (1993) replicated the findings of Elmes et al (1983), but demonstrated that the spacing effect in free recall also was eliminated with homogeneous lists that were affectively neutral. Thus, the spacing effect in free recall was eliminated when list words consisted entirely of four-footed animals or entirely of occupations.…”
supporting
confidence: 70%
“…Although other aspects of the findings reported by Elmes et al (1983), in conjunction with subsequent work (Elmes, Chapman, & Selig, 1984), suggested a complex relationship between affect and the spacing of repetitions, the elimination of the spacing effect with affectively homogeneous lists may have had more to do with the lists being homogeneous than with their affective characteristics. Kahana and Greene (1993) replicated the findings of Elmes et al (1983), but demonstrated that the spacing effect in free recall also was eliminated with homogeneous lists that were affectively neutral.…”
mentioning
confidence: 64%
See 3 more Smart Citations